Thin polymer films prepared by plasma immersion ion implantation and deposition - Rangel, E. C.; Silva, PAF; Mota, Rogério Pinto [UNESP]; Schreiner, W. H.; Cruz, N. C. (Elsevier B.V., 2005)
This work describes an investigation of the properties of polymer films prepared by plasma immersion ion implantation and deposition. Films were synthesized from low pressure benzene glow discharges, biasing the samples with 25 W negative pulses. The total energy deposited in the growing layer was varied tailoring simultaneously pulse frequency and duty cycle. The effect of the pulse characteristics on the chemical composition and mechanical properties of the films was studied by X-ray photoelectron spectroscopy (XPS) and nanoindentation, respectively. Analysis of the deconvoluted C 1s XPS peaks demonstrated that oxygen was incorporated in all the samples. The chemical modifications induced structural reorganization, characterized by chain cross-linking and unsaturation, affecting material properties. Hardness and plastic resistance parameter increased under certain bombardment conditions. An interpretation is proposed in terms of the total energy delivered to the growing layer. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: plasma immersion ion implantation and deposition; mechanical properties; chemical composition